1998
DOI: 10.1001/archinte.158.15.1681
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup and Per-Protocol Analysis of the Randomized European Trial on Isolated Systolic Hypertension in the Elderly

Abstract: Background: In 1989, the European Working Party on High Blood Pressure in the Elderly started the doubleblind, placebo-controlled, Systolic Hypertension in Europe Trial to test the hypothesis that antihypertensive drug treatment would reduce the incidence of fatal and nonfatal stroke in older patients with isolated systolic hypertension. This report addresses whether the benefit of antihypertensive treatment varied according to sex, previous cardiovascular complications, age, initial blood pressure (BP), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 33 publications
6
67
1
2
Order By: Relevance
“…42 However, the Syst-Eur trial evidenced a significant reduction in morbidity but not in mortality in this age group. 53 Gueyffier et al (1999), 54 in a meta-analysis of data from 1670 participants over 80, suggested that treatment of very old hypertensive patients prevented stroke by 34% (95% CI 8-52). Rates of major cardiovascular events and heart failure were significantly decreased, by 22% and 39% respectively.…”
Section: Treatment Of Hypertension In the Elderlymentioning
confidence: 99%
“…42 However, the Syst-Eur trial evidenced a significant reduction in morbidity but not in mortality in this age group. 53 Gueyffier et al (1999), 54 in a meta-analysis of data from 1670 participants over 80, suggested that treatment of very old hypertensive patients prevented stroke by 34% (95% CI 8-52). Rates of major cardiovascular events and heart failure were significantly decreased, by 22% and 39% respectively.…”
Section: Treatment Of Hypertension In the Elderlymentioning
confidence: 99%
“…6 -10 For example, treatment appears to be less effective in very elderly people with isolated systolic hypertension. 10 It is possible that people who survive to 80 years and older, a select group, might be somewhat tolerant of high blood pressure. The presence of target-organ damage in very elderly HT subjects would not be consistent with the notion that HT is a benign condition in this age group.…”
mentioning
confidence: 99%
“…7,11,12 In view of the remaining uncertainties with regard to the treatment of isolated systolic hypertension in the elderly, [13][14][15][16][17] the SystEur trial continued after the publication of the SHEP results. 9 Furthermore, the recent controversy on the role of calcium channel blockers as first-line antihy- pertensive agents 18,19 highlighted the lack of evidence that also this newer class of drugs could reduce cardiovascular risk.…”
mentioning
confidence: 99%